2006
DOI: 10.1051/0004-6361:20054376
|View full text |Cite
|
Sign up to set email alerts
|

The stellar masses of 25 000 galaxies at 0.2 z 1.0 estimated by the COMBO-17 survey

Abstract: We present an analysis of stellar mass estimates for a sample of 25000 galaxies from the COMBO-17 survey over the interval 0.2 < z < 1.0. We have developed, implemented, and tested a new method of estimating stellar mass-to-light ratios, which relies on redshift and spectral energy distribution (SED) classification from 5 broadband and 12 medium band filters. We find that the majority (>60%) of massive galaxies with M * > 10 11 M at all z < 1 are non-star-forming; blue star-forming galaxies dominate at lower m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

61
458
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 307 publications
(526 citation statements)
references
References 79 publications
61
458
7
Order By: Relevance
“…Bundy et al 2005Bundy et al , 2006Borch et al 2006;Pannella et al 2006). Ilbert et al (2010) performed similar analyses out to redshifts of z ∼ 2 and found that, for quiescent galaxies, z ∼ 1 represents an epoch of transition in their stellar mass assembly, showing that the stellar mass density for the quiescent population increases by over an order of magnitude from z ∼ 2 to z ∼ 0.8, but only increases by a factor of 2 between z ∼ 0.8 and the present day.…”
Section: Introductionmentioning
confidence: 86%
“…Bundy et al 2005Bundy et al , 2006Borch et al 2006;Pannella et al 2006). Ilbert et al (2010) performed similar analyses out to redshifts of z ∼ 2 and found that, for quiescent galaxies, z ∼ 1 represents an epoch of transition in their stellar mass assembly, showing that the stellar mass density for the quiescent population increases by over an order of magnitude from z ∼ 2 to z ∼ 0.8, but only increases by a factor of 2 between z ∼ 0.8 and the present day.…”
Section: Introductionmentioning
confidence: 86%
“…The stellar masses that we use were estimated by Borch et al (2006) using the COMBO-17 photometry in conjunction with a template library derived using the PEGASE stellar population models (Fioc & Rocca-Volmerange 1997) with solar metallicity and a Kroupa (2001) IMF. The different IMFs used by Whitaker et al and Borch et al would only change the stellar masses by ∼ 10%.…”
Section: Star Formation Ratesmentioning
confidence: 99%
“…Additionally 17-band COMBO-17 (Classifying Objects by Medium-Band Observations), Spitzer 24 μm, XMM-Newton X-ray data (Gilmour et al 2007) and gravitational lensing maps (Heymans et al 2008) are available. Photometric redshifts with errors δ z /(1 + z) ∼ 0.02 up to R = 24, spectral energy distributions (Wolf et al 2003) and stellar masses (Borch et al 2006) have been derived from the COMBO-17 survey as well as star-formation rates from the COMBO-17 UV and Spitzer 24 μm data (Bell et al 2007). Data from the Galaxy Evolution Explorer (GALEX), 2 degree Field (2dF) spectrograph, and Giant Meterwave Radio Telescope (GMRT) are also available.…”
Section: The Stages Data Setmentioning
confidence: 99%